Growth, Integration and Regional Inequality in Europe - George Petrakos; Andres Rodríguez-Pose; Antonis Rovolis (European Regional Science Association (ERSA), 2003)
This paper challenges the ability of the conventional literature initiated by Barro and Sala-i-Martin (1991, 1992) to detect actual convergence or divergence trends across countries or regions and suggests an alternative dynamic framework of analysis, which allows for a better understanding of the forces in operation. With the use of a SURE model and time-series data for eight European Union (EU) member-states, we test directly for the validity of two competing hypotheses: the neoclassical (NC) convergence hypothesis originating in the work of Solow (1956) and the cumulative causation hypothesis stemming from Myrdal's theories (1957). We also account for changes in the external environment, such as the role of European integration on the level of inequalities. Our findings indicate that both short-term divergence and long-term convergence processes coexist. Regional inequalities are reported to follow a pro-cyclical pattern, as dynamic and developed regions grow faster in periods of expansion and slower in periods of recession. At the same time, significant spread effects are also in operation, partly offsetting the cumulative impact of growth on space. Similar results are obtained from the estimation of an intra-EU model of inequalities at the national level, indicating that the forces in operation are independent of the level of aggregation. Our findings challenge the conventional wisdom in the European Commission about the evolution of regional inequalities and have important policy implications.
Keywords: 330